Efektivitas Aromaterapi dalam Menurunkan Kecemasan pada Pasien Percutaneous Coronary Intervention - Devie Dian Wahyuni; Elly Nurachmah (Journal of Telenursing (JOTING), 2023)
This study aims to identify the effect of aromatherapy on reducing anxiety in patients undergoing percutaneous coronary intervention (PCI), The research method uses a systematic review method by searching using six data bases from ProQuest, EBSCOhost, Science Direct, Clinicalkey Nursing, Scopus, Google Scholar. The database search found eight articles that were reviewed after being filtered based on inclusion and exclusion criteria. The results of systematic review show that aromatherapy can be used with a variety of aromas, and forms of aromatherapy oil, taking into account the amount of aromatherapy oil used, the distance of aromatherapy to the patient, and the exact time of administration. In conclusion, aromatherapy with several types can reduce anxiety level in patients undergoing PCI. Keywords: Anxiety, Aromatherapy, Percutaneous Coronary Intervention